The Values of Social Education Through Inter-Religious Dialogue in the Javanese Villages of Tomohon and Tumatangtang - Tarumingi, Denny Adri; Tombeng, Ineke; Sendow, Mieke Nova; Rintjap, Aurelia Nafra Sheren (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This research aims to analyze the values ​​of social education in the context of multiculturalism through interreligious dialogue in the Tomohon and Tumatangtang villages in Java. This type of research is qualitative with a case study approach. Data collection by interviews and observations. Data analysis uses triangulation. The research results are the values ​​of social education in the context of multiculturalism through interreligious dialogue in the villages of Tomohon and Tumatangtang Java, illustrating the importance of tolerance, mutual understanding, and interreligious cooperation in building a harmonious and inclusive society. Through this dialogue, people learn to respect religious and cultural diversity and develop a strong sense of brotherhood among themselves. Awareness of universal values ​​such as justice, compassion, and peace is the basis for strengthening relations between religious communities, creating an environment that allows mutual growth and progress within a framework of rich diversity.